Effect of Greywater Irrigation on Soil Characteristics - Anwar, Faisal (Institute of Electrical and Electronics Engineers (IEEE), 2011)
In this study, surfactant rich laundry greywater is used to investigate the changes of potential soil properties such as, hydraulic conductivity, porosity, pH, electrical conductivity and pressure-saturation relationship. A series of soil column (composed of several PVC rings) experiment was conductedunder unsaturated condition with varying greywater concentration and flow rate. In each experiment, pH, EC and hydraulic conductivity were measured. After greywater flushing in each experiment, the column was kept for 24 hrs to become equilibrium. The column was then dismantled and moisture content in each ring was measured gravimetrically and the soil pressure was taken as the distance of each ringfrom the reference groundwater level. The Break Through Curves with EC value and the measured value of pH at the column outlet revealed that the greywater with higher concentration reach the column outlet much faster. Soil hydraulic conductivity was found increasing steadily with greywater concentration but soil bulk density was found decreasing with greywater concentration. The porosity was first increasing and then found decreasing with greywater concentration. Pressure saturation curves showed that thecapillary rise decreases sharply with greywater concentration due the reduction of surface tension but remain constant after certain concentration which may be referred to the critical micelle concentration (CMC) of surfactants. All the interfaces are saturated with surfactant molecules at this CMC and itdoes not have any impact on further surface tension reduction. However, greywater irrigation may cause the water-repellent soil but it needs further investigation to confirm this statement.